Membudayakan Hidup Sederhana dan Menyantuni Dhuafa: Integrasi Dalil QS. Al-Furqān:67, QS. Al-Isrā’:26–30 dengan Konsep Zero Waste dan Circular Economy dalam Pendidikan Karakter Islam" - Nurfatimah Nurfatimah; Repa Susanti; Muhamad Yahya (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2026)
This study explores the integration of Quranic values of simple living and care for the less fortunate with the concepts of zero waste and the circular economy in Islamic character education. The research is motivated by increasing consumerism, excessive resource use, growing environmental problems, and declining social awareness, particularly among younger generations. Islam emphasizes moderation, responsible use of wealth, and concern for disadvantaged groups, as reflected in QS. Al-Furqān:67 and QS. Al-Isrā’:26–30. A qualitative library research approach was employed using the Quran, tafsir, hadith, and scholarly literature on character education, sustainability, zero waste, and the circular economy. Data were analyzed through interpretative analysis to identify the relevance of Quranic teachings to contemporary sustainability principles. The findings indicate that the Islamic principle of moderation aligns with zero waste practices by encouraging efficient resource use and minimizing waste. Likewise, the command to support the poor reflects the circular economy’s emphasis on resource redistribution, shared benefits, and social welfare. Integrating these values into Islamic character education can foster responsible consumption, effective waste management, generosity, and social empathy among students. This approach not only strengthens religious character but also develops environmentally conscious and socially responsible individuals capable of addressing modern sustainability challenges through the application of Islamic values in daily life.